Public Service Innovation as a Strategy for Increasing Regional Innovation in Probolinggo City - Arwanto Harimas Ginting; Adi Suhendra (Inovbook Publications, 2022)
This research is about innovation in the field of public services carried out by the City of Probolinggo.This research is important and relevant to be discussed because itThis innovation can solve problems from the aspect of limited funds for sanitation and technology development which are considered complicated andthe introduction of the SIBER-PAM strategy that can guarantee an increase in the quality of services for the community. Thus, the two innovations gave rise to various strategies that offer convenience in the use of public services.And can be an inspiration for other regions in order to overcome the same problem. The population in this study is in areas that have implemented policies orinnovation in the field of public services. While the sample in this study isinnovations carried out by the Probolinggo City government are called Si Inol Aja innovations (Innovation System for Arisan Services / Latrine Installments) and innovationsEasier Access Based on